Autism: a structure of existence and the legitimacy of subjects - Romano, Lucas Silva; Paravidini, João Luiz Leitão; Próchno, Caio César Souza Camargo (Clinical Styles. The Journal on the vicissitudes of childhood, 2019)
This article aims to extend the notion of the structure of the subject – understood as the effect of a contingent meeting, marked by the rupture and bound to the repetition – to the field of autisms, articulating it to its impact in the psychoanalytic approach of the people with autism. We present an investigation of the process that leads to the constitution of the speaker, associated with the hypothesis that the autism shows strong indications of a particular subjectivation process. Such a proposition focuses under the direction of treatment, as a way of approaching autistic subjects with a presence of calculated demand.